TIM3 and CTLA4 immune checkpoint polymorphisms are associated with acute myeloid leukemia in Saudi Arabia - Mashael Alqahtani; Ali Aljuaimlani; Jameel Al-Tamimi; Suliman Alomar; Lamjed Mansour (Hematology)
Background Immune checkpoints are receptors on the surface of T cells that function crucially in suppressing the immune response, and they are implicated in autoimmunity and cancer diseases.Aim The present study aimed to investigate the relationship between functional single nucleotide polymorphisms (SNPs) of two immune checkpoint molecules, CTLA-4 and TIM-3, and acute myeloid leukemia (AML) in a Saudi population.Methods Two SNPs in CTLA-4 (rs231775, A > G) and TIM-3 (rs10515746, A > C) were genotyped in 229 subjects, including 98 patients and 131 healthy controls, from the Saudi population using TaqMan assay methods. Differential expression of these two genes was performed using in silico analysis.Results An association was found between polymorphisms in TIM-3 (OR: 6.01; 95% CI: 3.99–9.05, P < 0.0001) and the risk of AML. Inversely, the rs231775 SNP in the CTLA-4 gene was found to protect against AML in allelic, dominant, and additive models (P < 0.05). A significantly higher expression of TIM-3 in the blood of individuals with AML was observed.Conclusion This is the first study focusing on single nucleotide polymorphisms (SNPs) for CTLA-4 and TIM-3 in acute myeloid leukemia patients in a Saudi community and could be a potential new prognostic factor for this disease.